Deteksi Cemaran Bakteri Coliform dan Escherichia coli pada Minuman Es Teh di Kota X - Pangesti, Adel Hening; Indrayudha, Peni (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Iced tea is a popular and refreshing beverage commonly sold by street vendors. However, because the production process utilizes water and relies on the level of hygiene during processing, there remains a risk of bacterial contamination. This study aims to determine the level of bacterial contamination, specifically Coliform and Escherichia coli, in iced tea samples sold in X City, in accordance with food safety standards. This study was conducted using the Most Probable Number (MPN) method with three dilution series. The presence of Coliform was identified using a presumptive test with Lactose Broth (LB) media and a confirmatory test with Brilliant Green Lactose Bile Broth (BGLB) media. The presence of Escherichia coli was identified using Eosin Methylene Blue Agar (EMBA) media and biochemical tests using Triple Sugar Iron Agar (TSIA) media. Samples were taken from 10 different locations spread across 5 subdistricts in X City, with 2 samples taken from each subdistrict. The results showed that there was Coliform bacterial contamination in 10 samples and Escherichia coli bacterial contamination in 6 of the 10 iced tea samples in X City with MPN values ranging from 3-460 MPN/100 mL. Based on the Mann-Whitney test, a p-value of 0.004 (p < 0.05) was obtained, indicating a significant difference in MPN values between Escherichia coli-positive and negative samples. These results indicate that all samples did not meet the microbiological quality requirements based on Peraturan Menteri Kesehatan Republik Indonesia No. 2 of 2023, which stipulates that the maximum allowable levels of total Coliform and Escherichia coli in drinking water is 0 MPN/100 mL.